Changes in executive function in the Canadian longitudinal study on aging over 3-years: A focus on social determinants of health - Stinchcombe, Arne; Hammond, Nicole G.; Hopper, Shawna (Frontiers in Psychology, 2023)
Maintaining executive functions, including planning, inhibition, and decision-making skills, is important for autonomy and activities of daily living. There is a growing body of evidence linking social determinants and cognitive aging, but less is known about the potential role of social determinants in changes in executive functioning over time. Using data from the Canadian Longitudinal Study on Aging (CLSA), a large cohort of mid-aged and older adults, we examined changes in executive function over a 3-year period. Specifically, we focused on the role of social determinants (i.e., social positioning, social support, education) in explaining these changes. Executive function was measured at baseline and follow-up three years later using the Mental Alteration Test (MAT). We computed a reliable change index (RCI) and used a multiple linear regression model to examine the associations between known correlates and change in executive function over the three-year period (n = 29,344). Older age, higher household income, and greater educational attainment predicted declines in executive function. Health factors (e.g., depression symptoms, physical activity levels) and many social determinants (sexual orientation, gender identity, race, and perceived social standing) were not associated with change in executive function. These results suggest that social determinants of health may be related to initial differences in cognitive functioning (i.e., cross-sectional differences) rather than more rapid cognitive aging.